Study of Use of Cable Cars as a Logistics Support to Rural Area in Garut, West Java - Wiku Larutama; Pebi Yuda Pratama; Sabrina Mutiara Fajrin (Universitas Pendidikan Indonesia, 2021)
Cable cars as a means of transporting goods and passengers have been applied in several countries. Cable cars can reach areas with difficult terrain to reach so as to support logistic systems for rural areas that have hard-to-reach terrain. The southern district of Garut Regency has extensive agricultural and plantation land and terrain that is quite difficult to reach so that the installation of cable cars will be able to provide the community with ease in transporting agricultural products. The existence of a cable car that has been installed in Sutenjaya Village, Lembang will facilitate development because it can be used as a pilot project.Cable cars as a means of transporting goods and passengers have been applied in several countries. Cable cars can reach areas with difficult terrain to reach so as to support logistic systems for rural areas that have hard-to-reach terrain. The southern district of Garut Regency has extensive agricultural and plantation land and terrain that is quite difficult to reach so that the installation of cable cars will be able to provide the community with ease in transporting agricultural products. The existence of a cable car that has been installed in Sutenjaya Village, Lembang will facilitate development because it can be used as a pilot project.